KLAUSA REDUKSI DALAM JURNAL ENGLISH TEACHING FORUM VOLUME 45 NO. 1 TAHUN 2007 - LUMIU, HUTRI ANGREINE; PAKASI, JENNY HILDA; LOTULUNG, DONALD RINGGO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ Â Â Â Â This study entitled â€œThe Reduced Clauses in the Journal of English Teaching Forum volume 45 No. 1 Year 2007 (A Syntactic Analysis)â€. The aim of this study is an attempt to identifying, classifying, and analyzing the function of reduced clause found in the journal. The data were taken from the journal based on the journal of English Teaching Forum.The method used in this study is descriptive method. There are three steps to finish this study, first the writer read some concepts related to the title about reduced clause and also browsed resources from internet. The second step is data collection. In collecting the data the writer read journal of English Teaching Forum in order to identify to all the reduced clauses in sentence. The results of this research show that the types of reduced clause found in this journal are reducedÂ adjective clause, reduced adverb clause and relative clauses. There are 39 of reduced clauses, which consist of 21 data of reduced adjective clauses, 17 data of reduced adverb clauses and 20 data of relative clauses. The study shows that reduced clauses are frequently used in journal specially in English Teaching Forum.Key Words: Reduced Clauses, Journal of English Teaching Forum, Syntactic Analysis.